2004
DOI: 10.1161/01.atv.0000147534.69062.dc
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Endotoxin as a Proinflammatory Mediator of Atherosclerosis

Abstract: Abstract-Atherosclerosis is increasingly recognized as a chronic inflammatory disease. Although a variety of inflammatory markers (ie, C-reactive protein) have been associated with atherosclerosis and its consequences, it is important to identify principal mediators of the inflammatory responses. One potentially important source of vascular inflammation in atherosclerosis is bacterial endotoxin. Mutations in Toll-like receptor 4 (TLR-4), an integral component of the endotoxin signaling complex, are fairly comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
200
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(214 citation statements)
references
References 182 publications
6
200
0
6
Order By: Relevance
“…The Bruneck study by Wiedermann et al in 1999 provided the first epidemiological evidence in support of a clinical association between levels of LPS and cardiovascular risk (145,146). Consistent with these findings, the role of bacterial endotoxin as a proinflammatory mediator of atherosclerosis has been widely reported for the HIVuninfected population (143). Studies on the role of bacterial bioproducts (i.e., LPS) and macrophage activators (sCD14) in the pathogenesis of atherosclerosis in HIV disease are under way, and discordant results have been generated so far.…”
Section: Microbial Translocation In Cardiovascular Diseasementioning
confidence: 68%
See 1 more Smart Citation
“…The Bruneck study by Wiedermann et al in 1999 provided the first epidemiological evidence in support of a clinical association between levels of LPS and cardiovascular risk (145,146). Consistent with these findings, the role of bacterial endotoxin as a proinflammatory mediator of atherosclerosis has been widely reported for the HIVuninfected population (143). Studies on the role of bacterial bioproducts (i.e., LPS) and macrophage activators (sCD14) in the pathogenesis of atherosclerosis in HIV disease are under way, and discordant results have been generated so far.…”
Section: Microbial Translocation In Cardiovascular Diseasementioning
confidence: 68%
“…The reasons for this phenomenon are likely complex, although recent studies suggested that chronic inflammation and immune activation/senescence may contribute to the initiation and progression of atherosclerosis in HIV infection (37,(140)(141)(142). LPS represents an important source of inflammatory stimuli (143) and has been investigated in the setting of atherosclerosis (144). The Bruneck study by Wiedermann et al in 1999 provided the first epidemiological evidence in support of a clinical association between levels of LPS and cardiovascular risk (145,146).…”
Section: Microbial Translocation In Cardiovascular Diseasementioning
confidence: 99%
“…[25][26][27][28] Given the involvement of NFkB signaling in atherosclerosis, LPS was used to activate it and stimulate the production of NFkBdependent pro-inflammatory cytokines. 29,30 Indeed, LPS caused a sustained activation of p65 in THP-1 macrophages ( Fig.…”
Section: Establishing Rap1 Knockdown In Thp-1 Macrophagesmentioning
confidence: 99%
“…Interestingly, LPS is found in the circulation of apparently healthy subjects [6,7] and its activity may be associated with highfat diet and dyslipidaemia. Infusion of triacylglycerol enhances LPS responses in humans, including the production of cytokines, suggesting that LPS can be locally released from lipoproteins in peripheral tissues through lipoprotein lipase action [8].…”
Section: Introductionmentioning
confidence: 99%